Epigallocatechin-3-gallate protected vanadium-induced eggshell depigmentation via P38MAPK-Nrf2/HO-1 signaling pathway in laying hens. (19th May 2018) - Wang, J; Yuan, Z; Zhang, K; Ding, X; Bai, S; Zeng, Q; Peng, H; Celi, P
ABSTRACT: It has been demonstrated that tea polyphenol (TP) epigallocatechin-3-gallate (EGCG ) can confer protection against vanadium (V) toxicity in laying hens; however, our understanding of the molecular mechanisms beyond this effect are still limited. In this study, 360 hens were randomly assigned to the 3 groups to study whether the potential mechanism P38MAPK-Nrf2/HO-1 signaling pathway is involved in the protective effect of EGCG on eggshell pigmentation in vanadium challenged laying hens. Treatments included a control group, a 10 mg/kg V (V10), and a V10 plus 130 mg/kg of EGCG group (V10+EGCG130). Both eggshell color and protoporphyrin IX were decreased in the V10 group compared with the control diet, while EGCG130 treatment partially improved shell color and protoporphyrin IX ( P < 0.05). The V10 exposure induced higher cell apoptosis rate and oxidative stress in birds as evidenced by the histological apoptosis status, decreased uterine glutathione-S transferase (GST) and high abundance of malondialdehyde (MDA) compared with the control group, whereas EGCG130 markedly alleviated oxidative stress via reducing MDA generation ( P < 0.05). Dietary vanadium reduced ferrochelatase, NF-E2-related factor 2 (Nrf2), and heme oxygenase (HO-1) mRNA expression, while EGCG up-regulated Nrf2 and HO-1 expression ( P < 0.05). Protein levels of Nrf2, HO-1 and phospho-p38 (P-P38) MAPK were reduced in V10 group, while dietary supplementation with 130 mg/kg EGCG markedly increased Nrf2, HO-1 and P-P38 MAPK protein levels in the uterus compared with the V10 group ( P < 0.01). In conclusion, EGCG improved eggshell color and antioxidant system in V10-challenged hens, which seems to be associated with P38MAPK-Nrf2/HO-1 signaling pathway.